Exploring possible topologies: scribbling movements in abakuá rituals - Lucena, Francisca Marcela Andrade (Cadernos de Campo (São Paulo, 1991), 2023)
The essay follows the different stages of the Plante ritual carried out by the abakuá society, a male brotherhood responsible for religious practices and social actions of mutual aid in Cuba. The essay shows a game between the external and internal dimensions present in the spatial movements formulated by the sacred during the aforementioned ritual. The photographs are always external and distanced and, from different points of view, capture the sacred Ceiba tree and the positions occupied by the abakuás in central moments of Plante. The diagrams, in turn, seek to retrace the ritual movements and directions (made only by men) and the positionalities of Ceiba, the temple and the women who observe the ritual externally. Diagrams and photographs then produce a topology specific to ethnographic work.